Investigating the Relationship between IL-6 Gene (Rs1800795) Polymorphism and Chronic Periodontitis in an Iranian Population: IL-6 Gene Polymorphism and Chronic Periodontitis - Vahabi, Surena; Saburi, Ehsan; Nazemisalman, Bahareh; Chalaki, Behzad; Shooshpasha, Hamid (Journal of Dental School, 2023)
Objectives Chronic periodontitis is the most common type of periodontitis and a multifactorial disease in which a set of factors such as microbial plaque, environment, systemic conditions and genetics play a role in its development. Periodontal destruction occurs due to the host's immune response to microbial stimulation, which can lead to tooth loss. The purpose of the present study is to investigate the correlation between IL-6 gene polymorphism (rs1800795) and chronic periodontitis in an Iranian population. Method This case-control analytical study was conducted on 54 patients with chronic periodontitis and 66 healthy individuals referred to the dental clinics of Shahid Beheshti, Zanjan, and Mashhad universities of medical sciences. After clinical examination and classification of subjects, blood samples (10 cc) were taken. The genomic DNA was extracted using salting-out method. The desired variant was amplified using PCR-RFLP method. Reaction products were analyzed after electrophoresis with 1% agarose gel. Data were analyzed with Pearson's chi-square and Hardy-Weinberg equilibrium tests, and P<0.05 was considered as the significant level. Results The frequency of GG, GC, and CC genotypes was 41%, 44%, and 15%, in the patient group, and 36%, 42%, and 21%in the control group, respectively. There was no significant difference between the two groups in terms of the distribution of any of the inheritance patterns (P>0.05). Conclusion The present study showed no relationship between IL-6 gene polymorphism (rs1800795) and chronic periodontitis in the studied population.